Microscopic pumping of viscous liquids with single cavitation bubbles. (10th August 2022) - Reese, Hendrik; Schädel, Robin; Reuter, Fabian; Ohl, Claus-Dieter
Abstract: Abstract : A cavitation bubble expanding and collapsing near a rigid boundary develops a directed jet flow towards the boundary. In the case of a perforated plate, some of the jet flow passes through the plate and thus the bubble acts as a pump transporting liquid from one side of the plate to the opposite side. The transport is rather complex, is time dependent and varies with the geometric parameters of the bubble and the connecting channel. Therefore, we first model the transport of liquid through a perforated rigid plate for a large range of parameters and then compare some regimes with experiments using single laser-induced bubbles. The simulations are based on a Volume-of-Fluid solver in OpenFOAM and account for surface tension, compressibility and viscosity. The resulting flux and generated velocity in the channel obtained in the simulations are discussed with regards to the dependence of the channel geometry, liquid viscosity and stand-off distance of the bubble to the plate. In general, high flow rates are achieved for long cylindrical channels that have a similar width as the jet produced by the collapsing bubble. At low stand-off distances combined with thick plates, an annular inflow creates a fast and thin jet, also called needle jet, which is approximately a magnitude faster and significantly thinner than the usually encountered microjet. In contrast, for thin plates and small stand-off distances, liquid is pumped in the opposite direction via a reverse jet .